Patterns of distribution and accumulation of trace metals in Hysterothylacium sp. (Nematoda), Phyllodistomum sp. (Digenea) and in its fish host Hoplias malabaricus, from two neotropical rivers in southeastern Brazil - Rosa Leite, Lucas Aparecido [UNESP]; dos Reis Pedreira Filho, Walter; Kozlowiski de Azevedo, Rodney; Doro Abdallah, Vanessa (Elsevier, 2021)
Here we evaluated the potential for trace metal accumulation of two parasitic species, Hysterothylacium sp. (Nematoda) and Phyllodistomum sp. (Digenea), found parasitizing Hoplias malabaricus, a characiform fish also known as trahira, collected from two neotropical rivers, Jacaré-Pepira and Jacaré-Guaçú, in southeastern Brazil. Fish were collected between July 2017 and July 2019, totaling 90 fish specimens analyzed, 45 from each river. From fish, we take samples of three different tissues: muscle, intestine and liver. Along with the parasite samples taken from fish hosts, tissue samples were analyzed by an Inductively Coupled Plasma Mass Spectrometer (ICP-MS) for obtaining the trace metal (Al, Cr, Mn, Fe, Ni, Cu, As, Cd e Pb) concentrations. All elements were found in statistically higher concentrations in the parasites, both nematodes and digeneans, than in the host tissues, but in comparison, was observed that Hysterothylacium sp. had higher concentrations than those obtained in Phyllodistomum sp. We also found that uninfected fish had statistically higher concentrations of metals than infected ones. And in those who are infected, the size of the parasitic infrapopulations correlated negatively with the concentrations of trace metals obtained in the hosts tissues, that is, the concentrations in fish showed a tendency to decrease as the parasitic infrapopulations increased, or vice versa. In addition, our results show that the influence of the parasitic infrapopulations on metal concentrations in the fish host is not affected in cases of mono-infection or co-infection.
Keywords: Accumulation indicators; Freshwater pollution; Heavy metal accumulation; Parasitic bioindicators; Water pollution